AB1321-HPR DEVELOPING A SELF-MANAGEMENT INTERVENTION TO MANAGE JOINT HYPERMOBILITY SYNDROME AND EHLERS-DANLOS SYNDROME HYPERMOBILITY TYPE: AN ANALYSIS INFORMED BY BEHAVIOUR CHANGE THEORY. (2nd June 2020) - Bennett, S.; Walsh, N.; Moss, T.; Palmer, S.
Abstract : Background: Joint Hypermobility Syndrome (JHS) and Ehlers-Danlos Syndrome Hypermobility Type (EDS-HT) are heritable disorders of connective tissue that can cause joint instability and pain and are associated with increased anxiety and depression. There is currently little UK guidance for supporting patients with JHS/EDS-HT 1 . The analysis presented here used the Behaviour Change Wheel (made up of the Theoretical Domains Framework (TDF) and Capability, Opportunity, Motivation and Behaviour (COM-B) model 2 ) to identify possible intervention options to improve self-management in people with JHS/EDS-HT. Objectives: To determine recommendations for the components of a behaviour change intervention for people with JHS or EDS-HT. Methods: Data from: 1) A systematic review and thematic synthesis of the literature examining adults' lived experiences of JHS/EDS 3 and 2) A thematic analysis of interview data where UK adults with JHS/EDS-HT (n=17, 14 women, 3 men) discussed the psychosocial impact of the condition on their lives 4, were mapped onto the TDF and COM-B in a behavioural analysis. A modified Nominal Group Technique focus group (n=9, all women) explored which interventions identified by the TDF/COM-B mapping exercise were most important to them. Results: Participants prioritised a range of potential self-management interventions, including: Education : Participants wanted greater support to improve their knowledge of JHS/EDS-HT, including self-help strategies for coping with injury, fatigue and overexertion, and how to evaluate information about their condition. Training : In activity pacing, assertiveness and communication skills, and what to expect during pregnancy, when symptoms of JHS/EDS-HT can worsen. Environmental restructuring and enablement: Support from occupational therapists to maintain independence at home. Enablement of access to CBT, mindfulness and emotional support. Modelled behaviour: Positive first-person narratives that address how other patients with JHS/EDS-HT have coped with anxiety, depression, distress, fear, frustration and feelings of loss. Conclusion: This study is the first to apply theoretically-informed approaches to the management of JHS/EDS-HT. Through a modified nominal group technique, potential behaviour change interventions for addressing barriers to self-management have been prioritised. Discussion with participants indicated poor access to psychological support, occupational therapy and a lack of knowledge of JHS/EDS-HT. Future research with healthcare professional and patient stakeholder groups will further evaluate which intervention options would be most acceptable and feasible for the management of JHS/EDS-HT. References: [1]Palmer, S., Terry, R. Rimes, K.A., Clark, C., Simmonds, J. & Horwood, J. (2016). Physiotherapy management of joint hypermobility syndrome – a focus group study of patient and health professional perspectives. Physiotherapy, http://dx.doi.org/10.1016/j.physio.2015.05.001 . [2]Michie, S., van Stralen, M.M. & West, R. (2011). The behaviour change wheel: A new method for characterising and designing behaviour change interventions. Implementation Science, 6(42). [3]Bennett, S.E., Walsh, N., Moss, T. and Palmer, S. (2019a) "The lived experience of joint hypermobility and Ehlers-Danlos Syndromes: A systematic review and thematic synthesis." Physical Therapy Reviews, 24 (1-2). pp. 12-28. ISSN 1083-3196 [4]Bennett, S.E., Walsh, N., Moss, T. and Palmer, S. (2019b) "Understanding the psychosocial impact of Joint Hypermobility Syndrome and Ehlers-Danlos Syndrome Hypermobility Type: A qualitative interview study." Disability and Rehabilitation . ISSN 0963-8288 Disclosure of Interests: None declared